200 - FAMILY CONTEXTUALIZATION: A REFLECTION ARTICLE ON CHILD NURSING CARE (Fiep Bulletin - online, 2011)
Discussions on value of family as an active element in the health-sickness process of child care have required that nursing professionals adopt new habits concerning the purpose of care, not focusing on the disease, but on the child and his or her family context. As a result, it's an article that reflects on the family, their context, structure and function, and incorporates this knowledge into the nursing practice, emphasizing knowledge, relationship and communication between nursing team and family. It indicates aspects, such as: the family today and their valuation in the nursing child care. It insists on the need of basing nurses' practice on the knowledge of family structure, functions and theories, what leads to the understanding of all changes occurred inside the family and contributes to care humanization, besides stimulating the nursing service to adopt an empathic attitude that involves warmth and co-responsibility.
Keywords: Pediatric Nursing; Family; Child's health